2013
DOI: 10.1586/17474124.2013.837264
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in acute liver failure: a review

Abstract: Acute liver failure is a rare and often devastating condition consequent on massive liver cell necrosis that frequently affects young, previously healthy individuals resulting in altered cognitive function, coagulopathy and peripheral vasodilation. These patients frequently develop concurrent acute kidney injury (AKI). This abrupt and sustained decline in renal function, through a number of pathogenic mechanisms such as renal hypoperfusion, direct drug-induced nephrotoxicity or sepsis/systemic inflammatory res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 71 publications
0
55
0
Order By: Relevance
“…In comparison, the degree of serum creatinine increase of Ն0.5 mg/dl from baseline appeared to be higher in our patients, with a correspondingly significant decrease in the estimated GFR at week 24. These results might be attributed to a number of pathogenic mechanisms, such as renal hypoperfusion, drug-induced nephrotoxicity, or systemic inflammatory response during severe acute exacerbation of CHB (33). However, there was no significant difference in the estimated GFRs between the TDF and the ETV groups over the treatment course, suggesting that the renal safety of TDF was the same as that of ETV for treating patients with severe acute exacerbation of CHB.…”
Section: Discussionmentioning
confidence: 92%
“…In comparison, the degree of serum creatinine increase of Ն0.5 mg/dl from baseline appeared to be higher in our patients, with a correspondingly significant decrease in the estimated GFR at week 24. These results might be attributed to a number of pathogenic mechanisms, such as renal hypoperfusion, drug-induced nephrotoxicity, or systemic inflammatory response during severe acute exacerbation of CHB (33). However, there was no significant difference in the estimated GFRs between the TDF and the ETV groups over the treatment course, suggesting that the renal safety of TDF was the same as that of ETV for treating patients with severe acute exacerbation of CHB.…”
Section: Discussionmentioning
confidence: 92%
“…Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry study, univariate and multivariate logistic analyses revealed that serum PCT concentration was a determinant of high serum Cr levels and low GFR, which indicated that elevated serum PCT might be one of the risk factors of renal injury in HBV-ACLF patients, just like tumour necrosis factor-α, interleukin-6, and interleukin-1 [17]. Furthermore, among the patients with elevated serum PCT (> 0.5 ng/mL), most showed particularly high serum Cr levels and low GFR.…”
Section: Figurementioning
confidence: 98%
“…Reduction in the effective circulating blood volume and subsequent hypoperfusion of the kidneys may be the possible pathogenesis of renal failure in patients with severe liver failure. 1 It is accompanied by renal vasoconstriction, which leads to a pronounced reduction in glomerular filtration rate (GFR). 2,3 The afferent arteriole has an important role in the regulation of renal blood flow and GFR, thus contributing to the control of extracellular fluid volume and arterial pressure.…”
Section: Introductionmentioning
confidence: 99%